Influence of Daily K-pop Watching Duration and Expenditure on K-pop Merchandise on Intention to Purchase Concert Tickets: Moderating Effect of Likeability Level - Wily Mohammad; Hanif Saifurrahman (International Journal of Management Science, 2023)
This quantitative study delves into the intricate landscape of K-pop fandom within the United States, particularly focusing on the influences that shape intentions to purchase concert tickets among individuals aged 15-29. With a carefully selected sample of 98 participants from a population of 65.47 million, this research employs the Structural Equation Model-Partial Least Squares (SEM-PLS) method to analyze secondary data sourced from a figshare dataset by Rraman (2020). The study's findings shed light on the diverse connections between K-pop-related factors and concert attendance intentions. Specifically, while "Expenditure on K-pop Merchandise" strongly and positively influences the intention to purchase concert tickets, "Daily K-pop Watching Duration" alone shows no significant impact. Intriguingly, when considering the moderating role of "Likeability Level," both these factors maintain their significance. The financial investment in K-pop merchandise remains a significant positive influence on concert intentions, further amplified by the positive significant moderating effect of "Likeability Level." But, the effect of “Daily K-pop Watching Duration” moderated by "Likeability Level" is not significant to “Intention to Purchase Concert Tickets.” These results underscore the multifaceted nature of K-pop fandom and its dynamic interplay with concert attendance intentions, contributing to a nuanced understanding of this vibrant cultural phenomenon.